Analysis of control, learn, and knowledge model for computer power management using unified modelling language - Candrawati, Ria; Hashim, Nor Laily (American Scientific Publishers, 2016)
This paper analyzes the human inactivity in the computer system and finds that; the reduction of the efficiency for the computer system power consumption can be ideal by the eligibility of the human inactivity period.This study reviews the self adaptation and control loop concept, and models a framework of a new method.The essential elements and features from these concepts were adapted and applied as an approach to a new implementation of Control, Learn, Knowledge Model.This study establishes a model of the theoretical framework and demonstrates it through a conceptual framework for the CLK.As a result, this study continues with proposing the analysis of CLK using UML model.